Taxpayer Compliance Determinants: An Empirical Study - Arief Himmawan Dwi Nugroho; Ardiani Ika Sulistyawati (Jurnal Akuntansi, 2019)
This study aims to find out and analyze the influence of tax socialization, understanding of tax procedures, age, type of work and tax sanctions on the compliance of taxpayers of private individuals in the district of Pedurungan. The type of research used is explantation research with quantitative approach. The population in this study is all taxpayers of private individuals registered in pedurungan subdistrict. Sample of 110 respondents with sampling method, namely accidental sampling method. Data analysis methods in this study include multiple linear regression analysis with dummy variables. The results showed that the socialization of taxation and understanding of tax procedures, had a significant effect on the compliance of taxpayers of private individuals. While the variable age, type of work, and tax sanctions have no significant effect on the mandatory compliance of private people.